Association of Midlife Inflammatory Markers With Cognitive Performance at 10-Year Follow-up - Kipinoinen Teemu; Toppala Sini; Rinne Juha O.; Viitanen Matti H.; Jula Antti M.; Ekblad Laura L. (LIPPINCOTT WILLIAMS & WILKINS, 2025)
Background and Objectives
Chronic low-grade inflammation, commonly associated with cardiovascular diseases and risk factors, has been associated inconclusively with cognitive decline and dementia. The aim of our study was to evaluate whether low-grade inflammation, measured in midlife, is associated with a decline in cognitive performance after a 10-year follow-up. We hypothesized that low-grade inflammation, estimated by interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-alpha), and high-sensitivity CRP (hs-CRP), is a predictor of cognitive decline in the general population.
Methods
This prospective cohort study is based on a Finnish nationwide, population-based Health 2000 Examination Survey, its supplemental examinations in 2000-2001, and the follow-up Health 2011 Survey. Cognitive performance at baseline and at follow-up was assessed with categorical verbal fluency (VF), word-list learning (WLL), and word-list delayed recall (WLDR). Baseline low-grade inflammation was measured with IL-6, TNF-alpha, and hs-CRP in 2001. Associations between low-grade inflammation and cognitive performance were analyzed with multivariable linear models adjusted for age, sex, education, APOE epsilon 4 genotype, type 2 diabetes, hypertension, hypercholesterolemia, body mass index, depressive symptoms, smoking, and baseline cognition.
Results
Nine hundred fifteen participants aged 45-74 years (median age 54 years, 55% women) were included in the analysis. Both higher IL-6 and TNF-alpha at baseline predicted poorer performance in VF and WLL at 10-year follow-up (VF: IL-6 beta: -1.14, p = 0.003, TNF-alpha beta: -1.78,p = 0.008; WLL: IL-6 beta: -0.61, p = 0.007, TNF-alpha beta: -0.86, p = 0.03). Elevated IL-6 also predicted a greater dedine in VF and WLL after a 10-year follow-up (VF: beta: -0.81, p = 0.01; WLL: beta: -0.53, p = 0.008). Baseline TNF-alpha did not predict cognitive decline, and hs-CRP did not predict cognitive performance or decline after 10-years.
Discussion
Our results suggest that low-grade inflammation in midlife is an independent risk factor for poorer cognitive performance later in life. Of the studied markers, IL-6 and TNF-alpha seem to be stronger predictors for cognitive performance and decline than hs-CRP.